The Effect of Good Corporate Governance on Tax Avoidance - Purnamasari, Dyah; Hadian, Niki; Rosanti, Shalsa (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine whether institutional ownership, board of commissioners, audit quality, and audit committee influence tax avoidance on coal mining sector listed on the Indonesia Stock Exchange for the period of 2016-2018. The factors tested in this study are institutional ownership, board of commissioners, audit quality, and audit committee as independent variables, while tax avoidance as the dependent variable. The research method used in this study is the explanatory method. The population in this study is the coal subsector company listed on the Indonesia Stock Exchange for the period of 2016-2018, amounting to 49 companies. The sampling technique used in this study was nonprobability sampling with a purposive sampling method, so that the sample size was 10 companies. Analysis of the data used in this study is multiple linear regression analysis at a significance level of 5%. The program used in analyzing data uses Eviews 9. The results of the partial research show that institutional ownership, independent board of commissioners, and audit committee influence tax avoidance. While audit quality has no effect on tax avoidance. In addition, the results of the study simultaneously show that institutional ownership, independent board of commissioners, audit quality, and audit committee influence tax avoidance. The magnitude of the influence of institutional ownership, the board of commissioners, audit quality, and audit committee in providing an influence contribution to tax avoidance of 83.7%.